2023
DOI: 10.3390/nano13061096
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Dependence of Poly (Vinylidene Difluoride) (PVDF) Rheological Performance on the Nano-Silica

Abstract: Research on the rheological performance and mechanism of polymer nanocomposites (PNCs), mainly focuses on non-polar polymer matrices, but rarely on strongly polar ones. To fill this gap, this paper explores the influence of nanofillers on the rheological properties of poly (vinylidene difluoride) (PVDF). The effects of particle diameter and content on the microstructure, rheology, crystallization, and mechanical properties of PVDF/SiO2 were analyzed, by TEM, DLS, DMA, and DSC. The results show that nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…For instance, it predicts that under lower values of , like those for magnetite Fe O ( ppm [ 33 , 34 , 35 ]) or NdFeB ( ppm [ 36 ]), let alone barium ferrite BaFe O ( ppm [ 37 ]), the magnetorotational mechanism of generating the electric response may become fully comparable with the magnetostrictive one and even exceed the effect of the latter. The same enhancement might be encountered as well if to deal with softer polymer matrices, like those of specially prepared PVDF films whose Young moduli range GPa, see [ 14 , 38 ]. Besides that, under a fixed direction of the applied field, even the sign of the effect might change, see the curves in Figure 5 .…”
Section: Discussionmentioning
confidence: 94%
“…For instance, it predicts that under lower values of , like those for magnetite Fe O ( ppm [ 33 , 34 , 35 ]) or NdFeB ( ppm [ 36 ]), let alone barium ferrite BaFe O ( ppm [ 37 ]), the magnetorotational mechanism of generating the electric response may become fully comparable with the magnetostrictive one and even exceed the effect of the latter. The same enhancement might be encountered as well if to deal with softer polymer matrices, like those of specially prepared PVDF films whose Young moduli range GPa, see [ 14 , 38 ]. Besides that, under a fixed direction of the applied field, even the sign of the effect might change, see the curves in Figure 5 .…”
Section: Discussionmentioning
confidence: 94%
“…Rheology is a recognized and effective technique for obtaining essential insights into the microstructure of polymer blends and composites, as evidenced by various studies [ 43 , 44 , 45 , 46 , 47 ]. Specifically, the prepared samples’ linear viscoelastic properties were investigated and illustrated in Figure 6 , Figure 7 , Figure 8 , Figure 9 , Figure 10 , Figure 11 and Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Rheology is a recognized and effective technique for the microstructure of polymer blends and composites, a [43,44,45,46,47]. Specifically, the prepared samples' line investigated and illustrated in Figure 6, Figure 7 Figure 6 shows complex viscosity (ղ*), storage modu versus frequency plots.…”
Section: Rheological Assessmentsmentioning
confidence: 99%
“…A review of the literature showed that studies on PVDF/PMMA blends investigated optical, mechanical, and thermal behavior, for instance stretching that may improve transformation of α into β phase in PVDF films [27][28]; however, there have been few systematic studies on electrical behavior [29]. Considering this, polymeric compounds made from PVDF and PMMA with different concentrations and solvents are fully described in this work.…”
Section: Introductionmentioning
confidence: 99%